(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze the correlation and agreement between end-tidal carbon dioxide (EtCO₂), transcutaneous carbon dioxide (TcCO₂), and arterial carbon dioxide partial pressure (PaCO₂) in patients receiving high-flow oxygen during apnoea in endoscopic vocal cord surgery. Subject and method: A prospective observational study was conducted on 130 patients undergoing endoscopic vocal cord surgery at the 108 Military Central Hospital from October 2022 to December 2025. All patients received general anesthesia with neuromuscular blockade, and airway management was performed using high-flow oxygen under apnoeic conditions. Paired measurements of EtCO₂, TcCO₂, and PaCO₂ were collected and analyzed to assess correlation and agreement. Result: A total of 130 patients were included, with a mean age of 47.3 ± 11.9 years. A total of 130 paired measurements of EtCO₂ and PaCO₂ and 810 paired measurements of TcCO₂ and PaCO₂ were recorded. EtCO₂ showed a strong positive correlation with PaCO₂ (r = 0.960, p < 0.001), with a mean bias of 5.38 mmHg and limits of agreement ranging from +0.82 to +9.94 mmHg (according to the Bland–Altman analysis). TcCO₂ also demonstrated a strong positive correlation with PaCO₂ (r = 0.987, p < 0.001), with a mean bias of 2.43 mmHg and limits of agreement from −1.57 to +6.43 mmHg (according to the Bland – Altman diagram). Conclusion: There is a strong positive correlation between EtCO₂, TcCO₂, and PaCO₂ in patients receiving high-flow oxygen during apnoeic endoscopic vocal cord surgery. TcCO₂ shows better agreement with PaCO₂ than EtCO₂ and may be a reliable non-invasive method for monitoring carbon dioxide levels in this setting.